THE EFFICACY AND SAFETY OF SECUKINUMAB 150MG REGIMEN IN TREATING PATIENTS WITH PSORIASIS VULGARIS - Tran Son, Tung; Hoang Thi, Phuong; Quach Thi, Giang; Le Thi Hai, Yen; Dang Thi, Luong; Trinh Thi, Linh; Nguyen Thi Mai, Huong; Dao Huu, Ghi; Pham Thi, Lan (Tạp chí Da liễu học Việt Nam, 2025)
Objectives: Evaluate the effectiveness and safety of secukinumab 150mg subcutaneous injection regimen in treating patients with moderate to severe psoriasis vulgaris. Subjects and methods: Prospective clinical trial on 32 patients with moderate to severe psoriasis. Patients were treated with secukinumab 150mg subcutaneous injection regimen for weeks 0, 1, 2, 3, 4, 8, 12, 16. Evaluate treatment response with PASI, DLQI and IGA 2011 and record adverse effects during 16 weeks. Results: After 16 weeks of treatment, PASI and DLQI gradually decreased during the period. The proportion of PASI 75 responses was highest at week 12 with 90.7%, while the proportion of PASI 90 and PASI 100 responses increased continuously until week 16, with 75% and 25% at week 16 respectively. There is a correlation between patients’ weight and the efficacy of the regimen. 3 cases (9.4%) experienced adverse effects, including fatigue, nasopharyngitis and shingles. Conclusion: Secukinumab 150mg regimen showed as an effective therapy with minor adverse events in the treatment of patients with moderate to severe psoriasis vulgaris. Received 11 November 2023 Revised 30 December 2023 Accepted 28 February 2024